Judgment and mercy : the turbulent life and times of the judge who condemned the Rosenbergs - Siegel, Martin J., 1966- (Three Hills, an imprint of Cornell University Press, 2023)
"The first biography of the federal judge Irving Robert Kaufman (1910-92). Kaufman presided over the atomic espionage trial of Julius and Ethel Rosenberg in 1951 and sentenced them to death. The book also examines Kaufman's rise from poverty, his work as a celebrated prosecutor, his landmark opinions expanding civil liberties, and his often tragic personal life"--